PL.10 Can the Institute for Healthcare Improvement "Model for Improvement" Reduce Obstetric Anal Sphincter Injuries (OASIS)?. (26th April 2013) - Maina, W; Mansfield, J; Jones, C; Tinsey, J; Cameron, M
Abstract : Introduction: Dr Foster reported obstetric anal sphincter injuries (OASIS) incidence in Norwich as 3.72% for spontaneous vaginal deliveries and 10.76% for instrumental deliveries against expected incidence of 3.6% and 7.6% respectively. The Norfolk and Norwich Improving Patient Safety (NNIPS) programme is modelled on Leading Improvement in Patient Safety (LIPS) programme (NHS Institute for Innovation and Improvement) which uses the Institute for Healthcare Improvement (IHI) Model for Improvement. Setting: UK university teaching hospital delivering 6000 babies annually. Aim: To reduce OASIS by 20% within nine months using IHI methodology. Methods: The nine month NNIPS programme involved four one day workshops and four mentoring sessions to equip teams with improvement techniques. Methodology employed in this project included: Ishikawa diagram Process mapping Model for Improvement: Plan-Do-Study-Act (PDSA) Statistical process control (SPC) charts for measurement Results: Ishikawa diagram – identified two issues: diagnosis and prevention. Process mapping identified up to four rectal examinations were required before OASIS diagnosis and no standardised technique of perineal examination. Redundant steps were removed and diagnosis was standardised in PDSA 1 and 2. Prevention: PDSA 3 involved the development of an agreed method of managing the perineum in second stage called "SLOWER."PDSA 4 involved group reflection with midwives. SPC Charts: failed to demonstrate any change in OASIS. Conclusion: We were unable to demonstrate any statistical reduction in OASIS although processes improved over the time frame.